Systematic review of methods for reporting combined outcomes after radical prostatectomy and proposal of a novel system: the survival, continence, and potency (SCP) classification. - Ficarra, V; Sooriakumaran, P; Novara, G; Schatloff, O; Briganti, A; Van der Poel, H; Montorsi, F; Patel, V; Tewari, A; Mottrie, A (2012)
CONTEXT: Although oncologic results remain the main outcome assessment for radical prostatectomy (RP), there is a need to include both urinary continence and potency recovery in the assessment of success for this procedure. Unfortunately, the widely used trifecta system does not weigh these outcomes differently. Moreover, the trifecta system-and even more so, the recently described pentafecta system-is only applicable in preoperatively continent and potent patients who receive bilateral nerve-sparing RP, and thus it is not an appropriate reporting tool for the majority of patients undergoing RP. OBJECTIVE: Perform a systematic review to evaluate critically the trifecta and pentafecta models and describe a novel system that can be used to report the most relevant intermediate- and long-term outcomes after RP. This system has increased generalizability by being applicable to all patients undergoing RP. EVIDENCE ACQUISITION: A literature search was performed in March 2011 using the Medline, Embase, and Web of Science databases. The Medline search included only a free-text protocol using the terms radical prostatectomy, trifecta, and pentafecta across the Title and Abstract fields of the records. Subsequently, the following limits were used: humans, gender (male), and language (English). The searches of the Embase and Web of Science databases used the same free-text protocol and the same keywords, applying no limits. EVIDENCE SYNTHESIS: Eleven original articles reported trifecta outcomes, and only one original article used the pentafecta model. These systems were correctly applied in only 28-62% of treated patients. A mean of 57% (range: 20-83%) of patients achieved continence and potency without prostate-specific antigen failure after RP. All the original articles were surgical series (level 4 evidence). The new proposed system categorizes the three outcomes using the letter S for biochemical disease-free survival, the letter C for urinary continence, and the letter P for potency recovery. This SCP system can be applied to all patients who undergo RP and is thus analogous to the use of the TNM system for classifying disease stage. Moreover, the SCP system allows us to distinguish four different clinical scenarios: (1) oncologic and functional success, (2) oncologic success and functional failure, (3) oncologic failure and functional success, and (4) oncologic and functional failure. CONCLUSIONS: The proposed novel SCP system offers the opportunity to appropriately classify all patients who undergo RP according to the oncologic and functional outcomes of relevance to them on an individual basis. We contend that this system's greater generalizability may make it more useful than the currently used trifecta and pentafecta systems, though its validation remains to be performed.